Hydrogen-bonded organic framework functionalized bismuth-based compound/Luffa sponge biochar: Construction of a novel hydrogel and its adsorption of dyes and heavy metal ions from wastewater - Miao Yu; Liwei Zhang; Xiaohong Wang; Yannan Xu; Xingli Wu; Jinxing Shu; Jingbo Wu; Chen Hao (Journal of Environmental Chemical Engineering, 2026)

Dopamine-induced interlayer bridging for enhanced through-plane thermal conductive performance of expanded graphite-based thermal interface materials - Yuyuan Fan; Long Gao; Jinxing Liu; Yajuan Zhong; Sufang Yang; Xueyao Feng; Hongtao Yu; Junfen Li; Xiaodong Tian; Lei Zheng; Xing Guo; Xi Yan; et al. (Chemical Engineering Journal, 2026)

Effect of Guide Vane Case on Hydrodynamic Performance and Unsteady Pressure-Pulsation Characteristics of Shaftless Pump-Jet Thruster - Taofeng Wang; Sanming Song; Liming Li; Jinxing Yu; Kaizhou Liu; Adam Rushworth; Xisheng Feng (Journal of Marine Science and Engineering, 2026)
Propulsors are essential power units for underwater vehicles and major sources of self-noise, with unsteady pressure pulsations linked to flow-induced noise. To study the impact of guide vane case on the hydrodynamic performance and pressure pulsation of a shaftless pump-jet thruster, six guide vane configurations were first compared under a reference operating condition of 600 rpm: a vaneless baseline, fixed vertical guide vanes, fixed forward-inclined guide vanes, fixed reverse-inclined guide vanes, co-rotating guide vanes, and counter-rotating guide vanes. Based on this comparison, the vertical-vane and counter-rotating-vane configurations were selected for extended operating-condition analysis under three rotational speeds and three inflow conditions. Transient numerical simulations were conducted using the SST k−ω turbulence model. The rotating regions were defined in a rotating reference frame, and the unsteady rotor–stator interaction was resolved using a transient sliding-mesh interface. Results show that the counter-rotating guide vane configuration achieves the highest head and efficiency among the tested cases, with a head of 1.8955 m and efficiency of 0.7306, representing increases of 19.64% and 22.87% over the fixed vertical guide vane case. The fixed forward-inclined guide vane exhibits the strongest thrust fluctuation and pressure pulsation. Pressure-pulsation intensity generally decreases from the impeller rim toward the central axis. Frequency-domain results indicate that most cases are dominated by the blade-passing frequency, whereas the counter-rotating guide vanes show a response nearly twice this frequency.

Selective ammonium enrichment in stopped-flow discharge operation of capacitive deionization (CDI) using a NiHCF/CNT electrode - Jui-Yao Chang; Yu-Hui Kao; Jinxing Ma; Chia-Hung Hou (Desalination, 2026)

Forward-Looking Sonar Based 6D Pose Estimation Using Acoustic-Yolo6D Detection and AnP Inversion: A Case Study for Subsea Christmas Tree Panel - Jinxing Yu; Sanming Song; Liming Li; Yuyang Lu; Taofeng Wang; Hairui Cao; Jiaxin Dong; Weilin Zang; Adam Rushworth; Bailu Si; Miaomou Chen (Journal of Marine Science and Engineering, 2026)
Subsea Christmas trees are often deployed in turbid coastal waters or seabed environments. During manipulator operations on Christmas tree panels, conventional optical servoing is severely limited by rapid electromagnetic attenuation and strong scattering from suspended particles, resulting in reduced visibility. Forward-looking sonar (FLS) provides stable imaging, but its unique imaging geometry and low resolution make direct 6D pose estimation challenging. To address this issue, this paper proposes a 6D object pose estimation method for FLS images, in which conventional optical control-point-based pose estimation is restructured to resolve the mismatch between optical-centric network assumptions and acoustic imaging characteristics, and is further integrated with acoustic projection-based pose inversion. First, to address the limited diversity of target appearances and the scarcity of training data, we construct an FLS imaging model based on primary truncation for image simulation, providing data for model pretraining. Second, a multi-task acoustic control-point detection network, Acoustic-Yolo6D, is designed to mitigate localization degradation caused by heavy speckle noise, low boundary contrast, and resolution variations associated with polar-coordinate imaging, through heatmap regression, auxiliary object segmentation, and explicit range-bearing positional encoding. An Acoustic-n-Point (AnP) model is then used to recover the target 6D pose. Finally, simulation and water-tank experiments on the socket target verify the feasibility and robustness of the proposed method under limited-data conditions. The method achieves a 3.1 cm mean translation error, a 10.88° mean orientation error, and 52 FPS in real underwater acoustic environments.

Efficient degradation of a sulfur mustard simulant by a hydrogen peroxide/guanidine system: mechanism and performance - Boren Xiao; Lingce Kong; Jinxing Yang; Yong Xu; Liang Yu; Lihong Qi (Environmental Geochemistry and Health, 2026)

Interpretable machine learning-based prediction of high abundance fishing grounds for albacore tuna (Thunnus alalunga) in the Indian Ocean - Chaochao Yu; Jinxing Xiao; Yangqin Ji (Regional Studies in Marine Science, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Analysis of odor and VOCs pollution in industrial parks of central inner Mongolia autonomous region based on mobile monitoring - Chaofei Li; Yuanhao Jia; Yu Qiu; Cheryl Marie Cordeiro; Sha Li; Yanying Chen; Jinxing Liu; Heinz W. Siesler; Hongkan Wu; Run Zhao (Atmospheric Environment, 2026)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Enlarged Perivascular Spaces (EPVS) Associated with Functional and Cognitive Outcome After Aneurysm Subarachnoid Hemorrhage (aSAH) - Haichao Wang; Qiuyue Yu; Wenyi Zhang; Shengqi Yao; Yun Zhang; Qiong Dong; Yichen Zhao; Jinxing Lin; Xueyuan Liu; Li Gong (Translational Stroke Research, 2025)

Immobilization of Pb in Alkaline Soil Amend with Nano-hydroxyapatite: Speciation, Bioavailability, and Bioaccessibility - Kai Che; Jinxing Yu; Yukun Ju; Xuan Zhao; Yunqian Gong; Chongming Chen (Bulletin of Environmental Contamination and Toxicology, 2025)

Interface gypsum deposition in flow-electrode CDI treating brackish water: Impacts and mechanisms - Liang Luo; Tao Liu; Jiazhou He; Jinxing Ma; Han-Qing Yu (Water Research, 2025)

Biochar immobilized Proteus mirabilis Ch8 to enhance the Cd phytoremediation potential of woody plant Robinia pseudoacacia L - Zhongliang Huang; Shuqi Niu; Xuejun Li; Jinlin Guo; Zihao Yang; Jinxing Zhou; Yuanlin Cheng; Yi Zhang; Lijuan Jiang; Jinlan Yu; Xuan Zhang; Hui Li (Journal of Environmental Management, 2025)

Investigation of Feeding Effects and Environmental Impact of Fish-Feed Quality: Evidence from Crucian Carp Feeding Experiments - Jiayin Wang; Ran Wu; Jianhua Wang; Jiangtao Guo; Ya Zhang; Nanbing Shi; Jinxing Gu; Yibing Han; Xinyi Guo; Zhe Yu; Guoxi Li; Zhenjiang Yang (Fishes, 2025)
The effects of three types of feed, purchased from online stores and having similar prices, on the growth performance and culture environment of crucian carp (Carassius auratus) were studied in this experiment, which aimed to provide a reference for the evaluation and selection of fish feed. The results showed that feeding different feeds had a significant effect on crucian carp, and that the growth-promoting effect of HD feed (feed produced by Haida Company Limited) was significantly better than that of the other two feeds. For example, the weight gain rate (WGR) of fish in the HD group was 47.1% higher than that in the LD group (p

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Greater variation of soil organic carbon in limestone- than shale-based soil along soil depth in a subtropical coniferous forest within a karst faulted basin of China - Tao Yang; Genzhu Wang; Jie Long; Jinyan Mi; Aijia Yu; Xingyu Liu; Haoran Zhang; Liang Dong; Zihao Li; Chenghao Zheng; Saman Herath; Jinxing Zhou; et al. (CATENA, 2024)

Influences of molecular composition in dissolved organic matter on its reactivity with chlorine radicals (Cl• and Cl2•−) - Shuer Li; Yu Lei; Jinxing Ma; Xin Lei; Xianhui Li; Xing Du; Yang Zhou; Xin Yang; Zhong Zhang (Chemical Engineering Journal, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Topography-driven differences in soil N transformation constrain N availability in karst ecosystems - Dongni Wen; Lin Yang; Kang Ni; Xingliang Xu; Longfei Yu; Ahmed S. Elrys; Lei Meng; Jinxing Zhou; Tongbin Zhu; Christoph Müller (Science of The Total Environment, 2024)

Characteristics of conserved microRNAome and their evolutionary adaptation to regulation of immune defense functions in the spleen of silver carp and bighead carp - Yinli Zhao; Jinxing Gu; Ran Wu; Bianzhi Liu; Pengsheng Dong; Guangqing Yu; Daoquan Zhao; Guoxi Li; Zhenjiang Yang (Fish & Shellfish Immunology, 2024)

Influence of filling mining on ground stability in a metal mine - Jianxin Yu; Siyang Liu; Zhibin Zhou; Huazhe Jiao; Jinxing Wang; Lianhao Zhou (Arabian Journal of Geosciences, 2024)

Phosphorus addition increases microbial necromass by increasing N availability in China: A meta-analysis - Haoran Zhang; Tao Yang; Xuejing Wu; Jianwei Zhang; Xiuying Yu; Jinxing Zhou; Saman Herath; Xiawei Peng (Applied Soil Ecology, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

Desorption performance of commercial zeolites for temperature-swing CO2 capture - Chongming Chen; Jinxing Yu; Guosheng Song; Kai Che (Journal of Environmental Chemical Engineering, 2023)

The impact of the urban digital economy on China's carbon intensity: Spatial spillover and mediating effect - Yu Cheng; Yue Zhang; Jingjing Wang; Jinxing Jiang (Resources, Conservation and Recycling, 2023)

Encoding CsPbX3 perovskite quantum dots with different colors in molecularly imprinted polymers as fluorescent probes for the quantitative detection of Sudan I in food matrices - Jinxing He; Lu Yu; Yandu Jiang; Lei Lü; Zhonghui Han; Xiaolei Zhao; Zhixiang Xu (Food Chemistry, 2023)

MgIn2S4@In2O3 hierarchical tubular heterostructures with expedited photocarrier separation for efficient visible-light-driven antimicrobial activity - Jinxing Yu; Peiyi Yan; Feng Chen; Shu Jin; Xiaoxiang Xu; Jun Qian (Chemical Engineering Journal, 2023)

Synergistic removal of organic pollutants from water by CTF/BiVO4 heterojunction photocatalysts - Yan Yu; Yanan Sun; Beixiao Ge; Jiawen Yan; Kaili Zhang; Hui Chen; Jinxing Hu; Juntao Tang; Shuang Song; Tao Zeng (Environmental Science and Pollution Research, 2022)

Damage behaviours of new-to-old concrete interfaces and a damage prediction model of reinforced concrete - Chuanqi Liu; Shenghao Zhou; Changxing Yu; Enlin Ma; Fanlei Kong; Xingrui Tang; Xuyang Gao; Xuanhao Zhang; Jinxing Lai (European Journal of Environmental and Civil Engineering, 2022)

Impacts of climate change on the global distribution of Cyclocarya paliurus - Zhaokui Du; Zichun Ren; Binbin Yu; Jinxing Zhu; Junmin Li (Biologia, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Mapping the permafrost stability on the Tibetan Plateau for 2005–2015 - Youhua Ran; Xin Li; Guodong Cheng; Zhuotong Nan; Jinxing Che; Yu Sheng; Qingbai Wu; Huijun Jin; Dongliang Luo; Zhiguang Tang; Xiaobo Wu (Science China Earth Sciences, 2021)

Techniques for detecting protein-protein interactions in living cells: principles, limitations, and recent progress - Yaning Cui; Xi Zhang; Meng Yu; Yingfang Zhu; Jingjing Xing; Jinxing Lin (Science China Life Sciences, 2019)

Novel FBN1 mutations are responsible for cardiovascular manifestations of Marfan syndrome - Jin’e Wang; Yupeng Yan; Jinxing Chen; Ling Gong; Yu Zhang; Mengmeng Yuan; Bing Cui; Yibo Wang (Molecular Biology Reports, 2016)

Fragment virtual screening based on Bayesian categorization for discovering novel VEGFR-2 scaffolds - Yanmin Zhang; Yu Jiao; Xiao Xiong; Haichun Liu; Ting Ran; Jinxing Xu; Shuai Lu; Anyang Xu; Jing Pan; Xin Qiao; Zhihao Shi; Tao Lu; et al. (Molecular Diversity, 2015)

Changes in chemical forms, subcellular distribution, and thiol compounds involved in Pb accumulation and detoxification in Athyrium wardii (Hook.) - Li Zhao; Tingxuan Li; Haiying Yu; Guangdeng Chen; Xizhou Zhang; Zicheng Zheng; Jinxing Li (Environmental Science and Pollution Research, 2015)

Stable carbon and hydrogen isotopes of gases from the large tight gas fields in China - JinXing Dai; YunYan Ni; GuoYi Hu; ShiPeng Huang; FengRong Liao; Cong Yu; DeYu Gong; Wei Wu (Science China Earth Sciences, 2014)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Surveillance and molecular characterization of Newcastle disease virus in seafowl from coastal areas of China in 2011 - Xiaoyuan Yuan; Youling Wang; Jun Li; Kexiang Yu; Jinxing Yang; Huaiying Xu; Yuxia Zhang; Hongbin Ai; Jinbao Wang (Virus Genes, 2013)

VKORC1 rs2359612C allele is associated with increased risk of coronary artery disease in the presence of coronary calcification - Yibo Wang; Jinxing Chen; Yu Zhang; Lv Bin; Kai Sun; Weifeng Yu; Jibin Liu; Channa Zhang; Haiqing Shen; Zhihui Hou; Fangfang Yu; Rutai Hui (Human Genetics, 2013)

Study of Lead Level During Pregnancy by Application of Synchrotron Radiation Micro XRF - Yongpeng Tong; Huibin Sun; Qi Luo; Jinxing Feng; Xiaohong Liu; Feng Liang; Fen Yan; Ke Yang; Xiaohan Yu; Yulan Li; Jianmin Chen (Biological Trace Element Research, 2011)

An ultradense genetic recombination map for Brassica napus, consisting of 13551 SRAP markers - Zudong Sun; Zining Wang; Jinxing Tu; Jiefu Zhang; Fengqun Yu; Peter B. E. McVetty; Genyi Li (Theoretical and Applied Genetics, 2007)